Analisis Penentuan Efisiensi Luas Tulangan Penampang Kolom Persegi Berdasarkan Orientasi Terhadap Denah Bangunan - Rizatul Aulina; Syafridal Is; Zainuddin Zainuddin (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
This study aims to determine the extent of the influence of column orientation or direction on the area of reinforcement to be used in building construction. The variables examined in this study were column orientation and reinforcement width. In the first analysis, the column orientation was tried with the X direction plan, so that the column dimensions b = 30 cm and h = 40 cm were obtained. The second analysis tried the column orientation with the Y direction plan, with the same column dimensions in order to obtain b = 40 cm and h = 30 cm. Structural analysis was performed with the help of SAP2000 version 20.2. The results showed that at the same construction with column orientation in X and Y direction, the axial load (Pu) and ultimate moment (Mu) were not much different. These results affect the area of reinforcement obtained from calculations based on the Mu value. The X direction column orientation obtained the value of Pu = -67240.86 Kg and Mu = 4001.97 Kgm with a reinforcing area of 2959.454 mm2. Whereas for the Y direction column orientation the value of Pu = -64776.95 Kg and Mu = 3306.4 Kgm with a reinforcing area of 3055.595 mm2. The percentage value (%) to X is Pu = -3,664%, Mu = -17,381%, and for As = 3,249%.